(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Preoperative anxiety is a clinical condition which requires medical management apart from reassurance. Surgical patients have the high incidence of anxiety. Relief from anxiety is accomplished by pharmacological and non-pharmacological measures, often there is no need of a therapeutic agents for control of preoperative anxiety. Various drugs are used for control of preoperative anxiety in the ward. Ayurveda has an age proved natural ways for the management of disease. Many Acharya have prescribed Rasayana and Aushadha for treatment of mental illness which is safe and effective under optimal doses. Method: Here is a study has been planned for Rogi Sambandhit Purva Karma in which administration of pre–operative medication and other measures are done to relieve the anxiety and other conditions. So, the present study is conducted to evolve an effective Ayurvedic drugs for management of preoperative anxiety. Here in this study Tagar Churna has been taken for study. Various ancient texts and online journals related to the topic have been reviewed. Result: Results were obtained by analysing the data using student’s t-test. Discussion: Discussions were done regarding entire clinical study and the results obtained with relative opinions and arguments.